Virtually international : how remote teams can harness the energy, talent, and insights of diverse cultures - Dodson, William R. (Emerald Publishing Limited, 2021)
Organizations have turned in droves to videoconferencing to augment operations, launch products, and reduce the costs of doing business. The digital transformation of industries has driven a boom in a global gig economy. Enterprises are tapping vast pools of freelancers and distributed staff around the world to reduce overhead, use talent they do not have in-house, and become agile. A new dawn of project- and team management has arrived. Virtually International speaks directly to corporate staff who find themselves propelled into managing projects with globally diverse teams of talent spread across countries and cultures. This book introduces readers to basic project management principles that will shorten learning curves and curtail the costs of managing international teams. Virtually International talks about what to look for in technology platforms and tools intended to facilitate the work of remote teams, and discusses how newly anointed home office workers can optimize home-working environments. This book lays out ways that virtual project managers can support productivity and enhance the well-being of geographically distributed team members. Virtually International also explores the cultural dimensions of working with professionals from ethnic, religious, and linguistic backgrounds different from that of co-workers. This is the book managers have been looking for to build globally diverse and inclusive teams of top talent. You can go to VirtuallyInternational.com to continue exploring practical ways of working effectively and problem-solving remotely across borders and cultures.